Compressive behavior of steel-reinforced concrete-filled circular steel tubular stub columns. (December 2020) - Zhang, Tao; Ding, Fa-xing; Liu, Xue-mei; Yu, Zhi-wu
Abstract: Steel-reinforced concrete-filled circular steel tubular (SRCFT) stub columns is a novel type of composite columns, which have a great potential to be used as piers or columns in practical engineering. Hence, it is essential to comprehend the compressive performance of SRCFT stub columns and suitably predict the compressive strength for the engineering design and applications. This paper aims to investigate the compressive behavior of SRCFT stub columns through combined experimental and numerical studies. A total of 8 specimens were tested to investigate the compressive performance of SRCFT stub columns in detail, in terms of the axial load-strain curve, ultimate bearing capacity, ductility, strength-weight-ratio and strain ratio. The SRCFT stub columns exhibited better ductility than CFT stub columns. The inserted steel section can effectively prevent shear cracks in the core concrete from propagating quickly. Furthermore, finite element model was established and verified by comparing the experimental and FE results. Then, the complex composite action among the steel tube, core concrete and steel section was discussed and clarified comprehensively. In addition, the capacity of the energy dissipation for SRCFT stub columns was discussed. Finally, a novel simplified formula was proposed to predict the ultimate bearing capacity of SRCFT stub columns. The studies may provide a considerable reference for designing this type of structures in engineering practice.